1998
DOI: 10.1080/026990598121927
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of two treatments for mild traumatic brain injury

Abstract: The purpose of this study was to compare an education-oriented single session treatment (SS) for mild traumatic brain injury (MTBI) to a more extensive assessment, education, and treatment-as-needed intervention (TAN). Participants were 111 adults with MTBI who were recruited from consecutive admissions to two hospital emergency wards. They were randomly assigned to either the SS or TAN modality. The groups did not differ on any demographic, injury-related, or questionnaire variable when first seen within 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 21 publications
3
89
0
1
Order By: Relevance
“…Of the 29 remaining studies, 18 were further excluded for similar reasons after the full text was thoroughly examined. Of these, 2 were considered as one complete study (Paniak, Toller-Lobe, Durand, & Nagy, 1998;Paniak, Toller-Lobe, Reynolds, Melink, & Nagy, 2000) because the original study had included a 1-yr follow-up published in a separate article. Therefore, the literature search yielded a total of 10 articles for inclusion in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 29 remaining studies, 18 were further excluded for similar reasons after the full text was thoroughly examined. Of these, 2 were considered as one complete study (Paniak, Toller-Lobe, Durand, & Nagy, 1998;Paniak, Toller-Lobe, Reynolds, Melink, & Nagy, 2000) because the original study had included a 1-yr follow-up published in a separate article. Therefore, the literature search yielded a total of 10 articles for inclusion in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning injury severity, studies on the mild TBI population (Paniak et al, 1998;Tiersky et al, 2005) showed no CI improvements. These 2 studies also showed little change in mean CIQ scores (20.52 and 0.29, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the clinic, any on-going problems are identified and appropriate assessments undertaken. It is known that 5% of even mild head injuries have significant disabling symptoms at 1 year and that appropriate management of mild TBI can reduce the incidence of these symptoms [24,25]. The aim of the clinic is to reassure patients and treat any persisting symptoms or complications.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, one evaluated a pharmacological intervention (DDAVP), 27 two evaluated activity restriction (full bed rest, 28 hospitalization 29 ), one evaluated head tomodensitometry v. admission, 30 four evaluated an information intervention (pamphlet, information session at the ED) [31][32][33][34] and seven evaluated diverse followup interventions (in neuropsychology, phone follow-up, etc.). 33,[35][36][37][38][39][40] Since the publication of the last systematic review, a small randomized controlled trial reported fewer headaches associated with hypertonic intravenous saline v. normal saline for 44 concussed children who needed intravenous access for CT-scan. 41 Ondansetron usage remained limited to patients who suffered from nausea following chemotherapy until a decade ago when research began to emerge supporting its use in children with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%